A patent review of antibiofilm fungal drugs (2002-present). (17th February 2021) - Serafini, Mairim Russo; Santos, Valdeene Vieira; Torres, Bruna Gaelzer Silva; Johansson Azeredo, Francine; Savi, Flávia Medeiros; Alves, Izabel Almeida
Abstract: Fungal biofilms, such as Candida albicans biofilms, are capable of surviving in hostile environments owing to their remarkable ability to adhere to surfaces and their tolerance to chemical interventions. Currently, therapeutic treatment options are few, making these biofilm-based infections problematic particularly due to their great tolerance to conventional antimicrobial drugs, thus causing serious health and economic problems. Therefore, the development of new drugs and antibiofilm specific therapies for the prevention and treatment of antifungal to eradicate biofilms are needed. This study was aimed at carrying out a patent review analysis to identify the innovation trends, and to explore the latest antifungal drugs and the specific therapeutic strategies available for the treatment of fungal biofilms. The present patent review was carried out using the Espacenet database, using the key words "biofilm and antifungal, " from 2002 to December 2019. Through this review, it was possible to identify that most of the patent contents refer to new synthetic drugs derived from natural products and associations thereof with existing antifungal drugs. Methods and biomaterials for the treatment and prevention of fungal biofilms, mainly for C. albicans biofilms, which is the most isolated and studied fungal species, were also disclosed. The lack of scientific and technical information on the biofilm eradication subject is remarkable and further confirmed by the small number of patents identified in this survey.